CP-070 The impact of hospital antibiotic guidelines on surgical prophylaxis in paediatric patients suffering upper and lower extremity injuries. (24th March 2015) - Sviestina, I; Mozgis, D
Abstract : Background: Surgical prophylaxis may account for 1/3 of all antibiotic use in paediatric hospitals and 80% of all antibiotic use in surgery. Appropriate surgical antimicrobial prophylaxis can prevent post-operative infection of the surgical site. Purpose: To evaluate antibiotic use for surgical prophylaxis in paediatric patients suffering upper and lower extremity injuries. Material and methods: Retrospective review of patients' medicines records before guidelines introduction in July/August and two months after in November/December 2013. Comparative analysis of the appropriateness of prophylaxis: number and percentage of patients who got prophylaxis on time, correct antibiotic dose and duration of prophylaxis. Results: Total number of patients: 201 in July/August and 81 in November/December. Prophylaxis was needed for 94 (47%) patients in July/August and 53 (65%) in November/December. 14 (15%) in July/August and 16 (30%) patients in November/December didn't receive prophylaxis although it was indicated in the guidelines. Prophylaxis was too early in 13 (16%) patients in July/August, 9 (24%) in November/December; on time: 40 (50%) in July/August and 17 (46%) in November/December, too late (started during or after surgery): 21 (26%) in July/August, 10 (27%) in November/December. No information about time: 6 (7%) in July/August, 1 (3%) November/December. 64 (87%) patients received a single dose in July/August and 32 (86%) in November/December; multiple doses within 24 h: 6 (8%) patients in July/August and 1 (3%) in November/December; prophylaxis >1 day: 7 (9%) patients in July/August and 4 (11%) in November/December. Cefazolin dose was too low in 16/79 (20%) patients in July/August and 3/37 (8%) patients in November/December. Conclusion: Although the guidelines were discussed and accepted by surgeons and there had been a two-month introduction period as well, only low positive trends were observed, with antibiotic treatment guidelines not having a major impact on antibiotic use. There is a need for new ways of promoting adherence to guidelines and appropriate antibiotic use. References and/or Acknowledgements: No conflict of interest.